The 4-hour body : an uncommon guide to rapid fat-loss, incredible sex, and becoming superhuman - Ferriss, Timothy (Crown Archetype, 2010)
The best-selling author of The 4-Hour Workweek outlines a program for healthy living that draws on 15 years of research and interviews with leading doctors and health-care experts to offer insight into genetic factors, nutrition requirements and fitness practices.